Limitações e considerações gerais para a concessão de medidas liminares, tutela cautelar e tutela antecipatória no processo civil - Souza, Victor Fernandes Cerri de (2015)
This monograph longs for to elaborate a general scenery on the injunctions and immediate injunctions, drawing for elementary parallel beginning that it composes the nuclear structure of the theme, leaving of the exam of the imperative of the positive law, under the aegis of the wide context of the general theory of the law, of the beginnings that orientate the central subject and of the hermeneutics impressions in respect of. Driving this text under the focus of the limits for the granting of injunctive and immediate injunctions in the intended business, this is connected in progressive scheme and in sequence it develops about the injunction, appraising itself and interposing their characteristics and essential aspects for the composition of the central theme. In order to detach the main statement this exhibition interposes its analysis to the limits for the concession of injunction in caution tutelage and in anticipatory tutelage, doing a general overview of the concerning legislation and evaluating its juridical effectiveness. It continues broaching, the assemblage of characteristics and presupposed for the concession of these measured in way to build a more complete and indispensable study to the composition of the enunciated theme, with the analysis of the periculum in mora and fumus boni iuris. It is still demonstrated the relevance of some determined juridical institutes for the complete understanding of the theme, and concluding the analysis its wrote a synthetic exam of the injunction in writ of mandamus and in the injunction action, of the effects of the repeal of the injunction, of the public civil action, of the reflexes of the thing judged in the understood interest and of the general characteristics of the premature tutelage